(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the correlation between criminal procedural law and moral norms. Crucially, it emphasizes the scientific dimensions of issues concerning the harmonization of criminal procedural legislation with moral and ethical standards. In this article, the analysis incorporates scholarly opinions as well as national and international legislation.